Analisis Hubungan Politik Utang Indonesia dan China Untuk Menghindari Debt Trap Diplomacy - Zhafarina Jauza Az Zahro; Faris Al-Fadhat; Andy Prasetiawan Hamzah (DINASTI RESEARCH, 2024)
The analysis of the political relationship of Indonesia's debt to China to avoid debt trap diplomacy discusses the political debt relationship between Indonesia and China, particularly considering the intensive cooperation and debt assistance that China has provided to Indonesia, as well as the establishment of loan condition regulations that threaten the use of the state budget as a payment tool. This writing aims to understand the development of Indonesia's debt to China, whether Indonesia is trapped in a Debt Trap, and how Indonesia can avoid Debt Trap Diplomacy. This research employs a qualitative descriptive analysis method, utilizing previously published sources with data collection sourced from books, journals, and other online media such as websites, databases, and information available on the internet. Based on dependency theory, it shows that loan conditions with high interest rates and strict repayment terms reflect unfavorable lending conditions. The increase in debt to China for the Indonesian economy can stimulate the country's growth, but a significant economic dependence can also make Indonesia more vulnerable to Debt Trap Diplomacy. The research results indicate that based on the analysis of Indonesia's debt to China, there has been a tendency for an increase over the past five years. Indonesia is also still in a position of safe debt ratios, both by national and global standards, and does not fall into the category of Debt Trap Diplomacy. Several steps, approaches, and diplomatic efforts have also been undertaken by Indonesia to avoid Debt Trap Diplomacy.